The Socialization Of Perma Number 5 Of 2019 Concerning Guidelines To Address Applications For Marriage Dispensation As An Effort To Prevent Child Marriage In Boyolali - Ngazizah, Inna Fauziatal (Institut Agama Islam Negeri (IAIN) Kudus, 2022)
The purpose of the stipulation of Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation is to overcome problems regarding applications for marriage dispensations in the Religious Courts. The reality that is happening in society is actually increasing. Based on this, this activity aims to determine the extent of public understanding about the impoartance of the marriage age limit, and to prevent child marriage in Boyolali through socialization of Supreme Court Regulation Number 5 concerning Guidelines for Adjudicating Applications for Marriage Dispensation. The analytical methodology used in this study is juridical-sociological with complementary data which is the distribution of information through interviews with informants through several question indicators described in the discussion. The results of this study indicate that people do not fully understand the importance of the age limit for marriage. So that the socialization of Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation is necessary to suppress child marriage rates for Boyolali.